The Effect of Project-Based Learning Making Dioramas from Inorganic Wastes on Elementary School to Enhance Student's Conceptual Understanding and Creativity - Rudin, Raka Bachtian; Raharjo, Tri Joko; Budi Utomo, Kamsidjo (Journal of Primary Education, 2021)
This study aims to determine the effect of Project-Based Learning on students' conceptual understanding and creativity. In this study, students will carry out a diorama project made from inorganic waste with the theme of the diversity of Indonesian society. This research is quantitative in the form of a Quasi-Experiment type One Group Pretest-Posttest Design. The selection of research samples using cluster sampling techniques. The number of respondents was 97 fourth-grade students at two elementary schools in Subang Regency. This research was conducted using blended learning considering the pandemic situation when the research was carried out. The data collection technique is triangulation which consists of tests, observations, and documentation. The data analysis used was N-Gain analysis, simple regression test, and hypothesis testing. The results obtained prove that there is a significant effect between the Project-Based Learning model on students' conceptual understanding and creativity. This is supported by the research findings on the T-Test about the effect of Project-Based Learning on conceptual understanding, it was found that t-count 9.32 > t-table 1.68 which showed a significant effect. Furthermore, the results of hypothesis testing using the T-test the effect of Project-Based Learning on creativity obtained tcount 9.29 > t-table 1.68 which shows there is a significant effect. The resulting Pearson correlation is 69% which is categorized as a strong influence. This is due to Project-Based Learning, which is an active learning model, so that students can freely express ideas in preparing projects, and there are new learning experiences that can add insight. Based on analysis, can be concluded that the Project-Based Learning can significantly affect on the student ability to understand conceps and creativity.